Role of biochemical and inflammatory markers in assessing COVID-19 severity among the Indian population: An observational study - Reema Kapoor Mehra; Prakriti Gupta; Navpreet Singh (Journal of Research in Clinical Medicine, 2022)
Introduction: Different laboratory parameters get altered in coronavirus disease 2019 (COVID-19); therefore, the changes of these parameters could help recognize the patients with severe disease. This study was conducted to achieve a comprehensive biochemical and inflammatory profile of COVID-19 among the Indian population. Methods: The study consisted of 730 patients admitted to Jaya Arogya Hospital, Gwalior, with COVID-19 from August 2020 to December 2020. The patients were divided into mild disease group (MDG) (n=533) and severe disease group (SDG) (n=197) depending on certain criteria, and their biochemical and inflammatory markers were collected. Data were analyzed using SPSS version 25. Results: Statistically significant rise in blood urea (P=0.011), serum creatinine (P=0.008), serum bilirubin (P=0.012), interleukin 6 (IL-6) (P<0.001), and troponin I (P<0.001) was observed in SDG as compared to MDG. Serum electrolytes (sodium and potassium) and serum protein (total protein and albumin) showed a significant fall in SDG as compared to MDG (P<0.001 for electrolytes and P=0.023 for proteins). The area under the receiver operating characteristic curve (AUROC) showed a high diagnostic value of IL-6. Conclusion: Patients with severe COVID-19 showed a high prevalence of hyperbilirubinemia, hypoproteinemia, electrolyte imbalance, and raised inflammatory markers (IL-6, troponin I, and procalcitonin). Results showed their effectiveness in assessing disease severity and predicting outcomes in patients with COVID-19.